Innovation and the growth of service firms: The Polish case - Krzysztof Szczygielski; Wojciech Grabowski; Richard Woodward (Center for Social and Economic Research (CASE), 2013)
Differences in the growth of firms remain a major topic in economics and strategy research. In this paper we investigated the link between innovation performance and employment growth. First we discuss the problem from the theoretical point of view and then we analyze the relationship between innovation performance and the dynamics of employment in the Polish service firms in 2004-2009. Firms that introduced new services or marketing techniques experienced stronger growth. Process innovations contributed to employment reduction. Tellingly, this effect could only be observed in 2008-2009, a subperiod which saw the lowest levels of aggregate demand. This conclusion yields support to the presumption formulated by Pianta (2005) that the impact of innovation on employment growth depends on the macroeconomic situation.
Keywords: D22; L25; L80; O33; 330; Poland; services; innovation; firm growth; quantile regression; Innovation; Innovationsmanagement; Erwerbstätigkeit; Dienstleistungssektor; Polen